The effect of locally braking crank rotation during pedaling on the pedaling force and activation of lower limb muscles - Iwata, S. (Journal of Science and Cycling, 2019)
Introduction: In competitive cycling, pedaling efficiency is one of the key factors and it can be improved by the smooth pushing, pulling back and pulling up movements. Considering the mechanisms of human adaptive movements, we devised an approach to improving pedaling efficiency (fig. 1). This study aimed to clarify the effect of locally braking crank rotation during the pull up phase on the pedaling force and activation of lower limb muscles.